2021
DOI: 10.1073/pnas.2024221118
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic depletion of Iran’s aquifers

Abstract: Global groundwater assessments rank Iran among countries with the highest groundwater depletion rate using coarse spatial scales that hinder detection of regional imbalances between renewable groundwater supply and human withdrawals. Herein, we use in situ data from 12,230 piezometers, 14,856 observation wells, and groundwater extraction points to provide ground-based evidence about Iran’s widespread groundwater depletion and salinity problems. While the number of groundwater extraction points increased by 84.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 21 publications
0
89
0
Order By: Relevance
“…Vahidipour et al (2021) concluded that the saltwater intrusion from the Bakhtegan Lake could threaten the groundwater resources in its coastal aquifers. Other studies also suggest the saltwater intrusion is a main contributor of groundwater degradation in different parts of Iran (e.g., Ebrahimi et al, 2016;Gorgij and Moghaddam, 2016;Bahrami Jovein and Hosseini, 2017;Ranjbar and Mahjouri, 2018;Noori et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Vahidipour et al (2021) concluded that the saltwater intrusion from the Bakhtegan Lake could threaten the groundwater resources in its coastal aquifers. Other studies also suggest the saltwater intrusion is a main contributor of groundwater degradation in different parts of Iran (e.g., Ebrahimi et al, 2016;Gorgij and Moghaddam, 2016;Bahrami Jovein and Hosseini, 2017;Ranjbar and Mahjouri, 2018;Noori et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…This is particularly true for the irrigation needs in Mediterranean climate regions, where the high irrigation water demands overlap with the dry season. As a consequence, Iran's agricultural expansion resulted in nonrenewable water harvesting due to the digging of a large number of deep and semi-deep wells (~750,000 wells), leading to a catastrophic decline in groundwater levels across the country (Maghrebi et al, 2020;Noori et al, 2021). The overexploitation of groundwater has deteriorated the IGWR through salt-rich water intrusion induced by non-equilibrium hydraulic gradient between fresh and saline groundwater resources (Ebrahimi et al, 2016;Motallebian et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations